Real-world survival patterns and multimodal therapy utilization in small cell lung cancer: a retrospective cohort study in a Chinese countryside hospital - Huang, Taosheng; Ma, Linjie; Wang, Mingfang; Pang, Xumei; Xu, Jiying; Chen, Xi; Xia, Yutao; Yan, Min; Zhao, Wenxiang; Cheng, Congcong; Wang, Runqing; Sun, Kai; et al. (Frontiers in Oncology, 2025)
IntroductionSmall cell lung cancer (SCLC) accounts for 13–15% of all lung malignancies and remains a highly aggressive disease with limited therapeutic progress, particularly in rural settings. Despite advances such as immune checkpoint inhibitors and multimodal therapy, real-world evidence on treatment utilization and survival outcomes in developing regions is scarce. This retrospective cohort study aimed to evaluate survival patterns and multimodal therapy use in SCLC patients from a Chinese countryside hospital.MethodsA total of 132 patients diagnosed with SCLC at Weifang Yidu Central Hospital between 2014 and 2023 were retrospectively analyzed. Patients were classified as limited-stage (LS) or extensive-stage (ES) using the Veterans Administration Lung Study Group (VALG) system. Clinical data, including demographics, treatment regimens, and outcomes, were collected. Overall survival (OS) and progression-free survival (PFS) were calculated using the Kaplan-Meier method, and subgroup analyses assessed the effects of platinum sensitivity, prophylactic cranial irradiation (PCI), concurrent chemoradiotherapy (CCRT), and palliative radiotherapy.ResultsOf 132 patients (64 LS-SCLC, 68 ES-SCLC), most received first-line platinum–etoposide regimens, with diminishing treatment continuity in later lines due to cumulative toxicities. Median OS was significantly longer in LS-SCLC than ES-SCLC (50.2 vs. 16.8 months, p<0.05). PCI reduced brain metastases (0% vs. 27%) and improved OS (50.2 vs. 36.4 months; HR=0.47), though not statistically significant. CCRT achieved longer OS than sequential chemoradiotherapy (54.9 vs. 50.2 months; HR=0.54). In second-line therapy, platinum-sensitive patients benefited from platinum rechallenge (median OS 17.7 vs. 12.5 months, p<0.05), whereas platinum-resistant patients showed no improvement. Palliative radiotherapy in ES-SCLC prolonged PFS (16.1 vs. 7.8 months) and OS (30.2 vs. 16.1 months) with near-significant trends (HR≈0.5).DiscussionThis real-world study confirms that concurrent chemoradiotherapy (CCRT) and prophylactic cranial irradiation (PCI) confer survival advantages in LS-SCLC, while palliative radiotherapy yields potential benefits in ES-SCLC. Platinum sensitivity remains a crucial predictor of second-line treatment efficacy, supporting reintroduction of platinum in sensitive relapses per guideline recommendations. Conversely, irinotecan–lobaplatin combinations provided limited benefit. Findings emphasize the need for personalized treatment sequencing and improved access to standardized multimodal care in rural healthcare settings.